The impact of diverse level of manure application on the chemical properties of the soil - Kazberuk, Witold; Rutkowska, Beata; Szulc, Wiesław (Polish Journal of Agronomy, 2021)
The aim of this study was to determine the effect of various methods of introducing manure in to the soil on the chem- ical properties of the soil. The field experiment was carried out in the Podlasie voivodship on a sandy soil. Cattle manure was ap- plied in a dose of 30 Mg ha-1 and mixed with the soil using a disc harrow or plowed into the depth of 10 and 20 cm. In soil samples, the content of available forms of phosphorus, potassium, mag- nesium, copper, sulfur, boron, manganese, zinc, iron and the soil reaction was determined. The results confirmed the influence of depth of manure application on soil properties. As the cultivation depth increased, the content of phosphorus and organic carbon in soil increased, C/N ratio expanded, but the content of magnesium and potassium in soil decreased. No effect of the cultivation depth on the soil pH value and the content of nitrogen, boron, zinc and sulfur was found. The results of the study indicate a different rate of manure changes in soil and the related need to develop ferti- lizer equivalents depending on the manure application method.